A study on Gender Differences in the Performance of Leadership Traits in Chinese Internet Promotion Service Industry - Yao, Ling; Wu, Jingjing; Rudnák, Ildikó (Acta Carolus Robertus, 2023)
Today, with the rapid development of China’s economy, leadership is an important factor in promoting the progress of enterprises. And leadership traits accompanied by the complexity of gender differences further affect organizational climate and business performance. In the traditional concept, men are more inclined to be leaders because they have some stereotyped leadership traits that people think leaders should have, but with the advance of modernization in open innovation, this stereotyped impression has gradually changed. Many modern scholars with open and innovative thinking believe that the characteristics of masculinity are no longer applicable to the contemporary market and working environment, but feminization and neutralization are more welcomed by most employees. The purpose of this survey is to clarify the performance of leadership traits reflected in gender differences among personnel in the Internet promotion service industry in Guangdong Province, China. This includes comparing the leadership traits of the physiological and psychological gender self-assessment of all participants (leaders and non-leaders) and all leaders. Here, Independent-Samples T-Test and One-Way ANOVA in SPSS are implemented in data analysis. The results show that about 1/3 of the 34 leadership traits were significantly different in physiological gender, but few traits were significantly different in psychological gender.